Sistem Pendukung Keputusan Pemilihan Perangkat Umum Persmabimed Berbasis Web dengan Metode Profile Matching - Abi Setiawan; Reza Nur Afdal; Shabrina Prabudi; Debi Yandra Niskah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Persmabimed is an organization under Universitas Negeri Medan that serves as a platform for students receiving the KIP-K scholarship and plays an important role in managing member activities and information. However, the selection process for general board members such as the chairman, secretary, and treasurer is still conducted manually and tends to be subjective, potentially leading to a mismatch between candidates and their assigned roles. This study aims to design and implement a web-based decision support system using the Profile Matching method to assist in the selection process of Persmabimed board members. The method is chosen for its ability to compare candidate profiles with ideal profiles based on GAP values and criterion weights. Data was collected through observation, interviews with organization administrators, and literature studies. The selection process involves calculating core and secondary factors, followed by ranking based on a weighted combination of hard and soft skills. The system’s results demonstrate that the Profile Matching method can produce objective and accurate decisions, selecting Irvan Affandi as chairman, Dinda Rizky Fadilah as secretary, and Kiki Ratna Sari as treasurer. The system was developed using PHP and Bootstrap to ensure accessibility and streamline the selection process. This research improves efficiency and fairness in organizational decision-making and can be applied to similar organizations in the future.